Collaborative Job Training in Rural Areas - Gary Paul Green; Vealeria Galetto; Anna Haines (Journal of Research in Rural Education, 2003)
We examine collaborative efforts by employers to provide job training in rural areas and assess how this collaboration affects the willingness of employers to train workers. Data are drawn from a telephone survey conducted in 2001 of a stratified random sample of 1,590 nonmetropolitan firms in the U.S. The literature on job training suggests that the primary reason why individual employers provide little general training is the "free labor contract." Workers are free to move from one firm to another, thus jeopardizing employers' ability to realize the returns from those investments. Employers are most likely to identify common skill requirements or develop training programms with other firms in their same industry; and are least likely to collaborate with firms in their marketing/ supply chain. Collaboration among firms is positively correlated with the percentage of the workforce that is formally trained and per capita expenditures for formal training. Finally, small businesses and manufacturing firms are much less likely to participate in these collaborative efforts.